Clinical Characterization of Anti-GQ1b Antibody Syndrome in Childhood - Cai, Lianhong; Hu, Zhanqi; Liao, Jianxiang; Hong, Siqi; Kong, Lingyu; Chen, Li; Luo, Yetao; Li, Tingsong; Jiang, Li (Frontiers in Pediatrics, 2021)
Objective To delineate the comprehensive clinical features of anti-GQ1b antibody syndrome in childhood. Methods The clinical data of children diagnosed with anti-GQ1b antibody syndrome at two Chinese tertiary pediatric neurology centers were collected and analyzed. We also conducted a systematic literature review on anti-GQ1b antibody syndrome in children. Results This study included 78 children with anti-GQ1b antibody syndrome, consisting of 12 previously unreported cases from the two Chinese centers. The median onset age was 10 years (range, 2–18 years). The most common phenotype was acute ophthalmoparesis (32%), followed by classic Miller Fisher syndrome (15%) and Bickerstaff brainstem encephalitis (12%). External ophthalmoplegia (48%), sensory disturbance (9%), and bulbar palsy (9%) were the three most frequent onset symptom manifestations. Brain or spinal lesions on MRI and abnormal recordings by nerve conduction study were present in 18% (12/68) and 60% (27/45) of cases, respectively. There was CSF albuminocytologic dissociation in 34% of the patients (23/68). IV immunoglobulin alone or combined with steroids or plasma exchange was administered to 58% of patients (42/72). We did not find a significant correlation between early improvement up to 3 months and age onset and phenotype. All patients showed different degrees of recovery, and 81% (57/70) had complete recovery within 1 year. Conclusions Acute ophthalmoparesis and classic Miller Fisher syndrome are the most common phenotypes of anti-GQ1b antibody syndrome in childhood. The majority of patients show good response to immunotherapy and have favorable prognosis.